The great ice battle - Abbott, Tony; Jessell, Tim (New York : Scholastic, 1999)
Jaffa City is frozen under the spell of Lord Sparr. Eric, Julie, and Neal join with Princess Keeah to battle the enemy in the biggest snowball fight of all time!
Keywords: Blessing and cursing -- Juvenile fiction; Fantasy fiction